2004
DOI: 10.1177/003172170408500514
|View full text |Cite
|
Sign up to set email alerts
|

The Heart of the Matter: Coaching as a Vehicle for Professional Development

Abstract: N SCHOOLS ACROSS the country, there is increased emphasis on coaching-a process whereby seasoned teachers provide instructional support, professional development opportunities, feedback, and materials to classroom teachers-as a central means to improve instruction and build the capacity of school staff members. Currently, a number of districts with low-performing schools have adopted coaching as a vehicle for the professional development of their teachers, a step that theoretically will translate into improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 0 publications
0
39
1
1
Order By: Relevance
“…Although there are promising indications that coaching may be an effective approach for improving teachers" language and literacy practices (Poglinco & Bach, 2004), there is little empirical support for its use, especially as an independent professional development strategy. That is, to date, coaching has been in combination with more formal training through coursework, or concentrated workshops (Sheridan, Edwards, Marvin, & Knoche, 2009).…”
mentioning
confidence: 99%
“…Although there are promising indications that coaching may be an effective approach for improving teachers" language and literacy practices (Poglinco & Bach, 2004), there is little empirical support for its use, especially as an independent professional development strategy. That is, to date, coaching has been in combination with more formal training through coursework, or concentrated workshops (Sheridan, Edwards, Marvin, & Knoche, 2009).…”
mentioning
confidence: 99%
“…. This is in contrast to several studies in the research literature describing how coaches are often pulled away from their coaching responsibilities to fulfill noninstructional duties (Campbell, 2007;Campbell & Malkus, 2009;Gibbons et al, 2010;Poglinco & Bach, 2004).…”
Section: Coach's Rapportcontrasting
confidence: 58%
“…Coaching is a popular strategy for professional development that increasingly more states and school systems are using to improve classroom instruction and enhance student achievement (Campbell & Malkus, 2011;Grant & Davenport, 2009;Knight, 2006;Poglinco & Bach, 2004). Coaching has been around almost 30 years (Dossey, 1984;National Research Council, 1989) originating from peer coaching where teachers observed and gave feedback to each other as they implemented new practices (Joyce & Showers, 1982).…”
Section: Chapter I Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly popular strategy for supporting the effectiveness of reading teachers, including those who provide intervention to struggling readers, is the provision of instructional coaching by a reading coach (see Dole, 2004;Poglinco & Bach, 2004). Coaching is usually characterized as a form of professional development that is individualized and sustained over time (International Reading Association, 2004).…”
Section: Instructional Coaching In Readingmentioning
confidence: 99%